Hardware e-Inventory management system / Tan Kit Huang - Tan , Kit Huang (2003)
Based on the concepts of e-Commerce and Enterprise Resource Planning (ERP) strategy, this project is to build a web-based Hardware c-Inventory Management System. The purpose of this project is to build an enhanced enterprise's inventory management system for all the Information Technology and Communication (ICT) Companies in Malaysia. Any user on any platform at any time will be able to retrieve or upload hardware inventory information through this system. This system will provide the control & management of inventory, ensuring the sufficiency of inventory, accuracy of data keeping and more profitable relationship with supplier. In order to produce a more efficient and better quality system, this project will be develop through several stages, by implementing the Waterfall Model methodology. The first two stages, which are requirement analysis and system design will be completed in the first semester. While for system coding, system testing, and system operation is completed in the second semester. This methodology approach was chosen because a web-based management system needs a well organized and structured planning of system design and implementation.